2022
DOI: 10.3390/jfb13020043
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Nanotubes Functionalized with Icariin for an Attenuated In Vitro Immune Response and Improved In Vivo Osseointegration

Abstract: Due to their superior mechanical and chemical properties, titanium (Ti) and its alloys have been widely used as orthopedic implantable devices. However, their bioinertness represents a limitation, which can be overcome by employing various surface modifications, such as TiO2 nanotube (TNT) fabrication via electrochemical anodization. Anodic TNTs present tunable dimensions and unique structures, turning them into feasible drug delivery platforms. In the present work, TNTs were loaded with icariin (Ica) through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 99 publications
(120 reference statements)
0
10
0
Order By: Relevance
“…It has been found that the presence of hydrophobic Chl‐a dye molecules on surfaces could reduce the interaction between aqueous electrolyte and catalyst surface [43] . Aside from this, PD presence on NT surface decrease the −OH groups density [44] and leads to an insignificant increase in contact angle value (52°). Contact angle found in NT/PD‐Chl is around 69° which sustains the presence of PD and Chl on the NT surface.…”
Section: Resultsmentioning
confidence: 96%
“…It has been found that the presence of hydrophobic Chl‐a dye molecules on surfaces could reduce the interaction between aqueous electrolyte and catalyst surface [43] . Aside from this, PD presence on NT surface decrease the −OH groups density [44] and leads to an insignificant increase in contact angle value (52°). Contact angle found in NT/PD‐Chl is around 69° which sustains the presence of PD and Chl on the NT surface.…”
Section: Resultsmentioning
confidence: 96%
“…These findings imply that TiO x -Au NCs (50:1) have the potential to be a useful and effective antibacterial agent for wound healing. In the study published in 2022, Negrescu et al explored the use of titanium dioxide nanotubes (TNT) loaded with icariin (ICA) through a layer of polydopamine (PDA) as a drug delivery platform for improved osseointegration in orthopedic implants [92]. As synthetic prerequisites for the fabrication of TiO 2 nanotubes, titanium plates were prepared through a process of mechanical polishing and cleaning.…”
Section: Titanium-based Nanoparticlesmentioning
confidence: 99%
“…Apart from iron or zinc oxide NPs, nanoforms of titanium dioxide are often investigated. A drug delivery platform consisting of titanium dioxide nanotubes loaded with ICA through a layer of PDA contributed to improved osseointegration in orthopedic implants [92], whereas flavonoid compounds adsorbed on FTNP revealed antiviral potential against coronaviruses HCoV 229E and SARS-CoV-2 [90]. The summary of the data related to connections of selected metal oxide nanoparticles with flavonoids, which were presented in the section, was included in Table 4.…”
mentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) is one such bioactive material that is reported to have the potential to induce angiogenesis. 3 The ability of TiO 2 to promote angiogenesis is attributed to the development of reactive oxygen species radicals on exposure to light. TiO 2 is commonly used as a photocatalyst owing to its strong oxidizing abilities, chemical stability, super hydrophilicity, nontoxicity, sturdiness, low cost, and transparency under visible light.…”
Section: Introductionmentioning
confidence: 99%
“…The use of bioactive materials in scaffolds is found to favorably increase vascularization without the need to add an external growth factor. Titanium dioxide (TiO 2 ) is one such bioactive material that is reported to have the potential to induce angiogenesis . The ability of TiO 2 to promote angiogenesis is attributed to the development of reactive oxygen species radicals on exposure to light.…”
Section: Introductionmentioning
confidence: 99%